Cloud computing bible - Sosinsky, Barrie A. (Wiley ; John Wiley [distributor], 2011)
Looks at what cloud computing is and is not, why cloud computing exists, and the value of cloud computing, along with information on cloud computing platforms, infrastructure, services, and security.